2022
DOI: 10.1155/2022/3606765
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in the Use of Hydrogels for Regenerative Medicine: Properties and Biomedical Applications

Abstract: Due to their particular water absorption capacity, hydrogels are the most widely used scaffolds in biomedical studies to regenerate damaged tissue. Hydrogels can be used in tissue engineering to design scaffolds for three-dimensional cell culture, providing a novel alternative to the traditional two-dimensional cell culture as hydrogels have a three-dimensional biomimetic structure. This material property is crucial in regenerative medicine, especially for the nervous system, since it is a highly complex and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 175 publications
0
26
0
Order By: Relevance
“…Through placing hydrogels at or near the wound areas, exosomes can be incorporated with hydrogels, which promotes better therapeutic effects and tissue repair [ 144 ]. Hydrogels do not have significant bioactivities by themselves, but employing hydrogels that have been loaded with EVs can increase their stability, and assist EVs in reaching the injured tissue for an extended in situ release [ 145 ]. Many investigations have shown that exosome-loaded hydrogels have a strong potential for use in the regeneration or repair of tissues [ 146 ].…”
Section: Strategies That Enhance the Therapeutic Effects Of Exosomesmentioning
confidence: 99%
“…Through placing hydrogels at or near the wound areas, exosomes can be incorporated with hydrogels, which promotes better therapeutic effects and tissue repair [ 144 ]. Hydrogels do not have significant bioactivities by themselves, but employing hydrogels that have been loaded with EVs can increase their stability, and assist EVs in reaching the injured tissue for an extended in situ release [ 145 ]. Many investigations have shown that exosome-loaded hydrogels have a strong potential for use in the regeneration or repair of tissues [ 146 ].…”
Section: Strategies That Enhance the Therapeutic Effects Of Exosomesmentioning
confidence: 99%
“…Applications of various hydrogels will be considered in regenerative and cellular medicine [ 144 , 145 ]. Various cells have been encapsulated into hydrogels to construct desired tissues and organs.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…On the other hand, multiple biomaterials can be integrated into chip devices, which play an important role in regulating the stiffness of the extracellular matrix and the composition of extracellular microstructures in physiological environments, thus contributing to the biological relevance of engineered tissue models 41–43 . Specifically, the employment of various natural polymeric hydrogel materials, such as silk, 44 collagen, 45 elastin, 46 hyaluronic acid (HA), fibronectin (FN), gelatine, 47 provides a designed 3D matrices for cell growth 48 .…”
Section: Overview Of Ooc Technologymentioning
confidence: 99%